Primary Ventricular Palliation in Hypoplastic Left Heart Syndrome: A Case Report - Vaz, Giovana Ferreira; Carvalho, Marcos Barbosa Guimarães; Gomes , Maria Eduarda Santos; Silveira, João Vitor Mendes da; Paula, Leonardo Sardinha de; de Sousa , Mirna; Soares, Viviane (Brazilian Journal of Case Reports, 2026)
Hypoplastic Left Heart Syndrome (HLHS) is a complex congenital heart disease significantly contributing to neonatal mortality. It is characterized by the severe underdevelopment of left-sided heart structures, obstructing systemic circulation and necessitating a patent ductus arteriosus and atrial communication for survival. This case involves a 35-year-old hypertensive and diabetic mother who received prenatal care through the Unified Health System (SUS). HLHS was identified via two fetal echocardiograms during pregnancy. Delivery occurred by emergency cesarean section following 50% premature placental abruption. The neonate presented an Apgar score of 8/8, weighing 2080g, with a length of 46cm and head circumference of 31.5cm. Management began on April 20, 2023, through hybrid surgery, including a 7x24 mm ductal stent, bilateral pulmonary artery banding, and a pulmonary trunk banding. Notably, this was the first successful procedure of its kind in Goiás. Postoperatively, the patient overcame Acinetobacter-induced sepsis diagnosed on April 22, 2023. On September 10, hospitalization was required for nutritional failure, successfully managed with a nasoenteral tube. The patient is currently undergoing clinical follow-up and monitoring for sequelae following the second stage of surgical palliation. This case underscores the critical role of early diagnosis and advanced surgical interventions in improving neonatal survival and long-term outcomes.